Diamine modified polymeric membranes for hydrogen/carbon dioxide separation - Abdul Nasir, N.; Junaidi, Mohd Usman Mohd; Hashim, Nur Awanis; Mohamed Zuki, Fathiah; Mohamad Nor, Mohamad Iskandr; Jan, Badrul Mohamed; Chong, Wen Tong (2018)
The separation of H2/CO2 is technologically crucial to produce clean and renewable H2-based energy. There are several established methods used to separate H2 from CO2, but membrane based separation is becoming more prominent due to high energy efficiency and cost effectiveness. However, separation efficiency of existing polymeric membranes is limited due to unfavourable diffusivity and selectivity between H2 and CO2. As such, research objective for this work is to investigate the effectiveness of diamine modification towards two different polymeric membrane materials, PSf and P-84, on their performance in H2/CO2 separation. The effects of different operating pressures and modification time on the permeance and selectivity are also studied. Comparison of pure and modified membranes will be further interpreted. The fabrication of membranes is done by using controlled evaporation method. Then, the prepared membranes will undergo diamine modification using BuDA for 10 and 30 minutes reaction times. All samples were analyzed by gas permeation test for separation performance and SEM and FTIR for membranes characterization. From SEM analysis, the images show that both polymers have defectfree surfaces and porous cross-section structures. FTIR spectra validate the cross-linking reaction by observing the existence of adsorption peak at 1529 cm-1. This specific characteristic peak implies the occurrence of C-N stretch within the membranes. The gas permeation test shows the respective modification towards P-84 and PSf for 10 and 30 minutes reaction times causes H2 permeability to increase drastically. Based on the experimental result, P-84 membrane with 10 minutes BuDA-modification reaction time and 5 bar operating pressure gives the best H2 permeability performance. By increasing the time to 30 minutes, the H2/CO2 selectivity of both polymers were increased to 4.97 and 6.09, respectively compared to its neat membranes.